(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The study and use of extremely tiny scale structures and materials is known asnanotechnology. Subnanometer to several hundred nanometer ranges are common for typicalmeasurements. A nanometer has a measurement of 109 m, or one billionth of a meter (nm). Tenhydrogen atoms or five silicon atoms aligned together would not be much longer than a nanometer.Nanotechnology is more than simply a continuation of miniaturization from the micron to the nanoscalescale, which allows for greater functionality in the same amount of area. Micrometer-sized materialsoften share bulk materials’ physical attributes, whereas nanometer-sized materials may have physicaltraits that are distinct from bulk materials. The modern electrochemical energy storage device, thesupercapacitor, has several advantageous properties, including high power density, quick charge rates,long-life cycle stability, high specific capacitance, and low cost. Nanostructured materials, such asmetals, metal oxides, and graphene nanosheets, have been increasingly employed in recent years forenergy storage. Electrode materials based on 2-Dimensional reduced graphene oxide have severaldesirable properties for use in supercapacitor electrodes, including large surface area, remarkableelectrical conductivity, good chemical stability, and excellent mechanical behavior.